WAYS TO IMPROVE THE METHODOLOGY OF TAX REVENUE FORECASTING AND PLANNING (Web of Discoveries: Journal of Analysis and Inventions, 2024)
This article presents possible prospects for increasing tax revenues by improving tax administration, factors affecting the increase / decrease in budget revenues, the main directions of tax reform, as well as relevant proposals and recommendations for increasing tax revenues to the state. budget.